Validation of Single Nucleotide Variant Assays for Human Leukocyte Antigen Haplotypes HLA-B*15:02 and HLA-A*31:01 Across Diverse Ancestral Backgrounds - Buchner, Amanda; Hu, Xiuying; Aitchison, Katherine J. (Frontiers in Pharmacology, 2021)
The human leukocyte antigen haplotypes HLA-B*15:02 and HLA-A*31:01 have been linked to life-threatening adverse drug reactions to the anticonvulsants carbamazepine and oxcarbazepine. Identification of these haplotypes via pharmacogenetic techniques facilitates implementation of precision medicine to prevent such reactions. Using reference samples from diverse ancestral origins, we investigated the test analytical validity (i.e., ability to detect whether or not the haplotypes were present or absent) of TaqMan assays for single nucleotide variants previously identified as potentially being able to “tag” these haplotypes. A TaqMan custom assay for rs10484555 and an inventoried assay for rs17179220 and were able to identify with 100% sensitivity and 100% specificity HLA-B*15:02 and HLA-A*31:01 respectively. A custom assay for rs144012689 that takes into account a neighboring single nucleotide variant with manual calling was also able to identify HLA-B*15:02 with 100% sensitivity and 100% specificity. A custom assay for rs106235 identified HLA-A*31:01 with 100% sensitivity and 95% specificity. The slight reduction in specificity for the latter was owing to another haplotype (HLA=-A*33:03) also being detected. While any positive call using the rs106235 assay could therefore be further investigated, as the presence of the HLA-A*31:01 haplotype confers adverse drug reaction risk, the absence of false negatives (indexed by sensitivity) is more important than false positives. In summary, we present validated TaqMan assay methodology for efficient detection of HLA haplotypes HLA-B*15:02 and HLA-A*31:01. Our data are relevant for other genotyping technologies that identify, or have the potential to identify, these haplotypes using single nucleotide variants.